Keanekaragaman Ikan di Sungai Luk Ulo Kabupaten Kebumen - Titik Tri Wahyuni; Agus Zakaria (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2018)
Freshwater fish is one of the biodiversity that build river ecosystem structure. Many human activities are carried out in the river as well as in the surrounding areas, such as removal of household waste, excessive fish exploitation and land use activities. This might changes river characteristics and lead to population and biodiversity decline.This research aim to 1) analyzethe diversity and species composition of fishin Luk Ulo River of Kebumen Regency,and 2) analyze the interaction among environmental factors with fish abundance in Luk Ulo River of Kebumen Regency. This research used survey method with cluster random sampling. The river was divided into three different region; upper-stream, middle-stream, and down-stream. Fish collected from 9 stations, i.e. 3 stations in the upper-stream, 3 stations in the middle-stream, and 3 stations in the down-stream. Morphology data were analyzed descriptively in order to make species description. The influences of environmental factor to species abundance were analyzed using Principal Component Analysis (PCA).The results showed that the number of fish obtained in this study were 72 individuals classified into 7 families and 13 species. The diversity and abundance of fish are influenced by physical and chemical factors ie temperature, TSS, pH, BOD5, COD, turbidity, DO, conductivity, salinity, current and substrate. BOD5 concentration was correlated positively with fish abundance with a correlation value of 0.540. In contrast, the effect of temperature and pH has a negative correlation to fish abundance with correlation values of -0.731 and -0.024. Dissolved oxygen (DO) and conductivity no effect on fish abundance.